2015
DOI: 10.15376/biores.11.1.1393-1406
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Polypropylene-Wood-Carbon Fiber Hybrid Composites

Abstract: Effects of the addition of short carbon fibers (CFs) on the mechanical, physical, and morphological properties of polypropylene (PP) and woodpolypropylene composites (WPCs) were investigated. Hybrid composites (mix of wood and CFs) were manufactured in a two-stage process, pellet extrusion and samples mold injection with varying amounts of poplar wood fiber (0%, 20%, 30%, and 40%) and CFs (0%, 3%, 6%, and 9%), with and without maleic anhydride grafted PP (MAPP) as a coupling agent. The composites were prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
(23 reference statements)
2
20
0
Order By: Relevance
“…This anomaly is typically attributed to the weighted average fiber length and the matrix compatibility and its influence on impact energy, similar observations were also reported by earlier studies 4,49 . The decrease in notched impact energy of PCF is related to the increased ability to form fiber‐matrix bridging, 24 similarly observed in the following inset's of Figure 4(a)‐(c). Also, in the case of MLF‐0° fiber slippage is observed around the fibers and polymer matrix, shown in the inset Figure 4(d)‐(f), this may lead to fiber pull out, and the resultant of high dissipation impact energy.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This anomaly is typically attributed to the weighted average fiber length and the matrix compatibility and its influence on impact energy, similar observations were also reported by earlier studies 4,49 . The decrease in notched impact energy of PCF is related to the increased ability to form fiber‐matrix bridging, 24 similarly observed in the following inset's of Figure 4(a)‐(c). Also, in the case of MLF‐0° fiber slippage is observed around the fibers and polymer matrix, shown in the inset Figure 4(d)‐(f), this may lead to fiber pull out, and the resultant of high dissipation impact energy.…”
Section: Resultssupporting
confidence: 86%
“…[14][15][16][17][18][19][20][21][22] Several authors have studied fiber-reinforced PP composites and have thoroughly investigated the influence of different fiber loading, dosing of coupling agents, and infill orientation on the thermal, morphological and mechanical properties. [23][24][25] However, none of these studies has addressed the significance of preliminary aspects of fiber material during 3D printing, that is, a detailed understanding between the influence of fiber-matrix compatibility, fiber length, and its distribution on the printed parts are missing.…”
Section: Introductionmentioning
confidence: 99%
“…The expected decrease in strength parameters was moderate. Similar to the addition of 20 wt% carbon fibers to PP tested by Kada et al [32], the addition of basalt fibers reduced water absorption compared to that of composites with wood fibers and stabilized strength properties in both tensile and flexural tests. The addition of the coupling agent MAPP also reduced water absorption because of the formation of covalent bonds of anhydride groups in MAPP with hydroxyl groups of cellulose; consequently, the polar functions of wood were no longer available for water molecules [33].…”
Section: Resultsmentioning
confidence: 65%
“…Furthermore, hybrid composites offer a better balance in mechanical properties than non-hybrid composites [3]. Nowadays, few studies have been conducted on the hybridization of wood-polymer composites (WPC) [4][5][6][7][8]. Guo et al reported that using a small amount of carbon fibers (e.g., 5-10 wt %) enhances mechanical properties of WPC and the usa-ge of wood fibers in carbon-fiber composites can reduce high cost while enhancing toughness [2].…”
Section: Hybrydowe Kompozyty Na Osnowie Polipropylenu Wzmacniane Włóknami Bazaltowymi I Węglowymimentioning
confidence: 99%